Endoscopy and MRI for restaging early rectal cancer after neoadjuvant treatment. (9th October 2022) - Stijns, Rutger C. H.; Leijtens, Jeroen; de Graaf, Eelco; Bach, Simon P.; Beets, Geerard; Bremers, Andre J. A.; Beets‐Tan, Regina G. H.; de Wilt, Johannes H. W.
Abstract: Aim: Chemoradiotherapy (CRT) has great potential to downstage rectal cancer. Response assessment has been investigated in locally advanced rectal cancer but not in early stage rectal cancer. The aim is to characterize the diagnostic accuracy of endoscopy performed by surgical endoscopists compared to (diffusion‐weighted, DWI) MRI only and a multimodal approach combining (DWI‐)MRI and endoscopic information both analysed by an abdominal radiologist for response assessment in early rectal cancer after neoadjuvant CRT. Materials and methods: Patients treated with neoadjuvant CRT for early distal rectal cancer (cT1–3 N0) followed by transanal endoscopic microsurgery were included. Three separate reassessment groups were analysed for response assessment using endoscopic evaluation alone versus (DWI‐)MRI alone versus the combination of endoscopy with (DWI‐)MRI with a focus on sensitivity and specificity and analysis using receiver operating characteristic curves. Results: Three cohorts ( N  = 36, N  = 25 and N  = 25, respectively) were analysed for response assessment. Of the endoscopy cohort, 16 of the 36 patients had a complete response. Area under the curve was 0.69 (0.66–0.74; pooled sensitivity 55.3%, pooled specificity 80.0%). Agreement for scoring separate endoscopic features was poor to moderate. Of the (DWI‐)MRI cohort, 11 of the 25 patients had a complete response. Area under the curve for (DWI‐)MRI alone was 0.55 (sensitivity 72.7%, specificity 42.9%). The areas under the receiver operating characteristic curve improved to 0.68 (sensitivity 90.9%, specificity 75.0%) when (DWI‐)MRI was combined with endoscopic information, with 11 out of 25 patients with a complete response. The most accurate response assessment was made by combining endoscopy and (DWI‐)MRI with a high negative predictive value (90.9%). Conclusion: Good and complete responders after chemoradiation of early stage rectal cancer can be best assessed using a multimodality approach combining endoscopy and (DWI‐)MRI.